Un análisis del desarrollo de las autonomías municipales en el federalismo argentino. El caso de la provincia de Córdoba - Marcelo Bernal, Roberto (2023)
This text is part of the author’s Ph.D. dissertation, which analyzes the level of development of municipal autonomous communities in Argentina, which were recognized by th e Constitution in 1994. This is a study of comparative federalism focused on subnational levels of government. The methodology used is to build a complex index that measures four of the country’s provinces. Measurements are related to the institutional, po litical, economic, administrative, and financial dimensions of the autonomy of local governments. This article presents the methodological strategy and the results of the analysis of the case of the province of Có rdoba, the district in which the autonomous powers of the municipality seem to have reached a higher level of development.